Investment in Improvement Strategies and Academic Achievement: The Case of Secondary Schools in Kenya - Jane Amunga (Foxton Books, 2020)
Secondary schools have adopted various strategies in an effort to improve performance. Collaboration and benchmarking are two such strategies. However, schools still continue to post poor grades in national examinations, an indicator that most of the students fail to meet the university cut off mark and thus fail to join university. This raises the question of whether such investment is really justified. This study sought to investigate whether investment in these two practices translated into improved education outcomes as measured by mean scores in the Kenya Certificate of Secondary Education. The study adopted correlation research design. From a target of 103 schools in the region involved in collaboration and benchmarking, 31schools were randomly selected. The sample comprised all 31 Directors of Studies and 31principals from the sampled schools. Data were collected using questionnaires with closed and open ended items, and document analysis. Data were analyzed inferentially (PPMCC and Multiple linear regression) using the Predictive Analytical Software (PASW) Version 19.0. The data on open ended items were coded using open coding, categorized and reported verbatim. Findings indicated that, investment in the two strategies significantly improved academic achievement (r=0.822; r2=0.676; adjusted r2=0.603). However, considered independently, investment in collaboration had a much higher impact on academic achievement (r=0.843, r2=0.711; adjusted r2=0.697), compared to investment in benchmarking (r=0.510, r2=0.260; adjusted r2=0.219). It is recommended that, schools should generously and uniformly invest in both collaboration and benchmarking in order to boost academic achievement. In addition, well endowed schools should be encouraged to share their resources.